Answer:
a) [tex] P(X=3) = 0.1[/tex]
b) [tex] P(X\geq 3) =1-P(X<3) = 1-P(X\leq 2) = 1-[P(X=0) +P(X=1)+P(X=2)][/tex]
And replacing we got:
[tex] P(X \geq 3) = 1- [0.2+0.3+0.1]= 0.4[/tex]
c) [tex] P(X=4) = 0.3[/tex]
d) [tex] P(X=0) = 0.2[/tex]
e) [tex] E(X) =0*0.2 +1*0.3+2*0.1 +3*0.1 +4*0.3= 2[/tex]
f) [tex] E(X^2)= \sum_{i=1}^n X^2_i P(X_i)[/tex]
And replacing we got:
[tex] E(X^2) =0^2*0.2 +1^2*0.3+2^2*0.1 +3^2*0.1 +4^2*0.3= 6.4[/tex]
And the variance would be:
[tex] Var(X0 =E(X^2)- [E(X)]^2 = 6.4 -(2^2)= 2.4[/tex]
And the deviation:
[tex] \sigma =\sqrt{2.4} = 1.549[/tex]
Step-by-step explanation:
We have the following distribution
x 0 1 2 3 4
P(x) 0.2 0.3 0.1 0.1 0.3
Part a
For this case:
[tex] P(X=3) = 0.1[/tex]
Part b
We want this probability:
[tex] P(X\geq 3) =1-P(X<3) = 1-P(X\leq 2) = 1-[P(X=0) +P(X=1)+P(X=2)][/tex]
And replacing we got:
[tex] P(X \geq 3) = 1- [0.2+0.3+0.1]= 0.4[/tex]
Part c
For this case we want this probability:
[tex] P(X=4) = 0.3[/tex]
Part d
[tex] P(X=0) = 0.2[/tex]
Part e
We can find the mean with this formula:
[tex] E(X)= \sum_{i=1}^n X_i P(X_i)[/tex]
And replacing we got:
[tex] E(X) =0*0.2 +1*0.3+2*0.1 +3*0.1 +4*0.3= 2[/tex]
Part f
We can find the second moment with this formula
[tex] E(X^2)= \sum_{i=1}^n X^2_i P(X_i)[/tex]
And replacing we got:
[tex] E(X^2) =0^2*0.2 +1^2*0.3+2^2*0.1 +3^2*0.1 +4^2*0.3= 6.4[/tex]
And the variance would be:
[tex] Var(X0 =E(X^2)- [E(X)]^2 = 6.4 -(2^2)= 2.4[/tex]
And the deviation:
[tex] \sigma =\sqrt{2.4} = 1.549[/tex]